Hereditary Myoclonus Dystonia: A Novel SGCE Variant and Phenotype Including Intellectual Disability - Coughlin, David G. (Tremor Other Hyperkinet Mov (N Y), 2018)
BACKGROUND: Hereditary myoclonus dystonia is often due to changes in the SGCE gene. Dystonia (DYT)-SGCE has a variable phenotype that can involve focal or generalized myoclonus and various forms of task-specific, segmental, or generalized dystonia. Psychiatric comorbidities are common. CASE REPORT: We report a case of a young woman with generalized myoclonus, dystonia, and intellectual disability. She was found to have a novel SGCE splice site variant. DISCUSSION: This novel variant is very likely pathogenic by in silico analysis and has not been previously reported. Additionally, her intellectual disability may constitute a novel phenotype for patients with SGCE variants.